Sodium-Calcium Exchangers in Rat Ameloblasts - Reijiro Okumura; Yoshiyuki Shibukawa; Takashi Muramatsu; Sadamitsu Hashimoto; Kan-Ichi Nakagawa; Masakazu Tazaki; Masaki Shimono (Elsevier, 2010)
Although the central role of ameloblasts in synthesis and resorption of enamel matrix proteins during amelogenesis is well documented, the Ca2+-transport/extrusion mechanism remains to be fully elucidated. To clarify Ca2+-transport in rat ameloblasts, we investigated expression and localization of Na+-Ca2+ exchanger (NCX) isoforms and the functional characteristics of their ion transporting/pharmacological properties. RT-PCR and immunohistochemical analyses revealed expression of NCX1 and NCX3 in ameloblasts, localized in the apical membrane. In patch-clamp recordings, Ca2+ efflux by Na+-Ca2+ exchange showed dependence on external Na+. Ca2+ influx by Na+-Ca2+ exchange, measured by fura-2 fluorescence, showed dependence on extracellular Ca2+ concentration, and it was blocked by NCX inhibitors KB-R7943, SEA0400, and SN-6. These results showed significant expression of NCX1 and NCX3 in ameloblasts, indicating their involvement in the directional Ca2+ extrusion pathway from cells to the enamel mineralizing front. Keywords:: transporter, enamel, mineralization, channel, SLC8 gene family